2021
DOI: 10.5114/biolsport.2020.97674
|View full text |Cite
|
Sign up to set email alerts
|

The first, second, and third most demanding passages of play in professional soccer: a longitudinal study

Abstract: The study aimed to compare the physical demands required during the first, second, and third most demanding passages (MDP) of play considering the effect of playing position, type of passage, and passage duration. A longitudinal study for three mesocycles was conducted in a professional soccer team competing in LaLiga123 . Tracking systems collected total distance covered (DIS), high-speed running distance (HSRD), sprinting distance (SPD), total of high-intensity accelerations (ACC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 33 publications
3
29
1
Order By: Relevance
“…In recent years, load monitoring in sport has evolved through the increasing use of Global Positioning Systems (GPS) [1][2][3]. Current GPS allow the measurement of velocity and acceleration through doppler-derived methods, which allow the quantification of external training and competition loads such as distance covered, the count of efforts and identification of peak speed [4][5][6][7]. Importantly, while external loads are not the stimulus for functional training adaptations, their measurement can provide a useful objective marker of physical performance output, which plays a role in managing the overall training process [8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, load monitoring in sport has evolved through the increasing use of Global Positioning Systems (GPS) [1][2][3]. Current GPS allow the measurement of velocity and acceleration through doppler-derived methods, which allow the quantification of external training and competition loads such as distance covered, the count of efforts and identification of peak speed [4][5][6][7]. Importantly, while external loads are not the stimulus for functional training adaptations, their measurement can provide a useful objective marker of physical performance output, which plays a role in managing the overall training process [8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of investigations on the physical demands of elite soccer players have been conducted [1][2][3][4][5] since the governing body of soccer, which is FIFA, allowed the use of electronic performance and tracking systems in official matches [6]. These investigations frequently analyze parameters such as total distance, high-speed running distance, a total of accelerations or decelerations performed by the players during the match because these parameters help coaches to adapt the training load and the training drills by having a better understanding of match demands [1][2][3][4][5]. However, elite soccer matches are characterized by fast paces of play which require high demands of perceptual-motor skills of the players (e.g., continuous interaction with teammates in a specific space and time to dribble the ball while considering the opposition players) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the analysis of the trunk accelerations through the G-forces experienced by the players may provide meaningful information about the players' performance [17,18]. Soccer is a team sport characterized by high-intensity actions (e.g., intermittent sprints, changes of direction, body impacts, jumps, and landings), which implies that measuring the trunk accelerations is necessary [1,2,19]. Since inertial sensors allow the quantification of the trunk accelerations in the three axes of movement, recent investigations have suggested the use of G-forces as an external workload indicator [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the performance in the WCS is associated with different contextual variables (e.g., playing position, match location, match outcome, match half or congested calendars) [ 4 , 5 , 9 12 ]. For example, the WCS in soccer matches could be specifically analysed with regards to the playing position [ 4 , 5 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the performance in the WCS is associated with different contextual variables (e.g., playing position, match location, match outcome, match half or congested calendars) [ 4 , 5 , 9 12 ]. For example, the WCS in soccer matches could be specifically analysed with regards to the playing position [ 4 , 5 , 9 , 10 ]. It has recently been observed that midfielders (MF) and wide midfielders cover greater distance in WCS than other positions [ 4 , 5 ], and when longer periods of WCS are analysed, there are even greater differences between playing positions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%